Alginate microparticles as carriers for the UV filter 2‐ethylhexyl 4‐methoxycinnamate: Influence on photostability. (20th November 2019) - Duarte, J.; Almeida, I.F.; Costa, M.; Da Silva, E.S.; Faria, J.L.; Sousa Lobo, J.M.; Costa, P.C.; Scalia, S.
Abstract: Objective: The organic ultraviolet UVB filter 2‐ethylhexyl 4‐methoxycinnamate (EHMC) was encapsulated in microparticles (MPs) of sodium alginate and co‐loaded with vitamin E (Vit.E) by an extrusion process using an aerodynamically assisted jetting (AAJ) methodology. The aim was to assess the effect of encapsulation concerning UVB filter release from the MPs and its photochemical stability. Methods: The EHMC photostability was analysed by exposing the samples (both MPs in aqueous dispersion and incorporated in a cream preparation) during 1 h to simulated solar light. For the MPs (empty‐MP, EHMC‐MP and EHMC + Vit.E‐MP), the morphology and size were characterized; while in the case of the encapsulated samples, the amount of EHMC‐loading was determined. The release of EHMC was evaluated by adding EHMC‐MP or EHMC + Vit.E‐MP to 65% ethanol in water under mechanical stirring at 32°C. Results: All MPs showed a homogeneous size distribution with a median of 90.5 ± 2.5 μm for EHMC‐MP and 70.4 ± 1.14 μm for EHMC + Vit.E‐MP. The encapsulation efficiency was 92.9% and 99.4% for EHMC‐MP and EHMC + Vit.E‐MP, respectively. The observed release from the MPs was lower than the dissolution of the pure UV filter. EHMC‐MP and EHMC + Vit.E‐MP were successfully incorporated into a cream formulation, with no evidence of phase separation or colour modification. Upon simulated light exposure, the photoisomerization/phototransformation of EHMC encapsulated in MPs and Vit.E‐MP decreased as compared to free EHMC, both in aqueous dispersion and as a cream. The conformational ratio of the isomers (Z‐/E‐EHMC) was found to be the lowest in the presence of Vit.E. Conclusion: This work demonstrates that use of these alginate microparticulate carriers could enhance the effectiveness of sunscreen preparations containing this UVB filter. Abstract : Sodium alginate was used for the first time as MP carrier for EHMC. UV filter loss by photodegradation was decreased when loaded in alginate‐based MP. Co‐loading with vit E leaded to the lowest ratio of the isomers Z‐EHMC/E‐EHMC. Résumé: Objectif: Le filtre ultraviolet organique D'UVB 2‐éthylhexyl 4‐methoxycinnamate (EHMC) a été encapsulé dans des microparticules (MPs) d'alginate de sodium et co‐chargé avec la vitamine E (Vit.E) par un processus d'extrusion utilisant une méthode de jet assisté aérodynamique (AAJ). L'objectif était d'évaluer l'effet de l'encapsulation concernant la libération du filtre UVB par les MPs et sa stabilité photochimique. Méthodes: La photostabilité EHMC a été analysée en exposant les échantillons (les deux MPs en dispersion aqueuse et incorporés dans une préparation de type crème) pendant 1 h à la lumière solaire simulée. Pour les MPs (MP‐vide, EHMC‐MP et EHMC ‐ Vit.E‐MP), la morphologie et la taille ont été caractérisées; tandis que dans le cas des échantillons encapsulés, la quantité de charge EHMC a été déterminée. Le relargage de l'EHMC a été évalué en ajoutant EHMC‐MP ou EHMC ‐ Vit.E‐MP à 65% d'éthanol dans l'eau sous agitation mécanique à 32°C. Résultats: Tous les MP ont montré une distribution homogène de taille avec une médiane de 90, 5 +‐ 2, 5 μm pour EHMC‐MP et de 70, 4 +‐ 1, 14 μm pour l'EHMC et Vit.E‐MP. L'efficacité de l'encapsulation était de 92, 9 % et 99, 4 % pour EHMC‐MP et EHMC ‐ Vit.E‐MP, respectivement. Le relargage observé des MPs était inférieur à la dissolution du filtre UV pur. EHMC‐MP et EHMC ‐ Vit.E‐MP ont été incorporés avec succès dans une formulation de crème, sans aucune preuve de séparation de phase ou de modification des couleurs. Après exposition à la lumière simulée, la photoiomérisation/phototransformation de l'EHMC encapsulée dans les MPs et Vit.E‐MP a diminué par rapport à l'EHMC libre, à la fois dans la dispersion aqueuse et la crème. Le rapport conformationnel des isomères (Z‐/E‐EHMC) s'est avéré le plus bas en présence de Vit.E.